Cardiopulmonary arrest caused by nafamostat mesylate during hemodialysis. Issue 7 (25th July 2022) - Shioya, Nobuki; Inoue, Nozomu; Sato, Hiroki; Iwahara, Motoko; Sato, Tomohiro; Tsukamoto, Yuki; Naito, Yuki; Hazama, Kohji; Shichinohe, Yasuo
Abstract: Dialysis‐related adverse reactions can be serious and difficult to predict. In our case, nafamostat mesylate (NM) was thought to be the cause of cardiopulmonary arrest (CPA) due to NM‐induced anaphylaxis but was not reflected in the allergy tests. Rare but life‐threatening drawbacks occur immediately after hemodialysis initiation. Abstract : Despite proper hemodialysis (HD), cardiac arrest may occur immediately after the start of HD owing to the use of anticoagulants and dialysis membranes. It is essential to be aware of this unpredictable complication and apply strict observations.